Pelaksanaan Implementasi Model Pembelajaran Inkuiri Berbantuan Media Audiovisual untuk Meningkatkan Hasil Belajar Ilmu Pengetahuan Sosial - Ramaili, Jumita; Prastowo, Andi (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
The research aims to analyze the application of the inquiry learning model assisted by audiovisual media to improve social studies student learning outcomes. The type of research is descriptive qualitative research, data collection techniques are carried out through; interviews, observation and documentation. The focus of the research is the inquiry learning model assisted by audiovisual student learning outcomes, followed by data analysis techniques using qualitative descriptive. The research results showed that student learning outcomes after using the audiovisual assisted inquiry learning model experienced changes and improvements in the good category. The researc h conclusion is that there has been an increase in student learning outcomes in social studies subjects through the application of inquiry and audiovisual. at the MI Ma'arif Bego school, Sleman district, Yogyakarta special region.